The NLRP3 inflammasome mediates DSS-induced intestinal inflammation in Nod2 knockout mice. Issue 2 (February 2019) - Umiker, Benjamin; Lee, Hyun-Hee; Cope, Julia; Ajami, Nadim J.; Laine, Jean-Philippe; Fregeau, Christine; Ferguson, Heidi; Alves, Stephen E; Sciammetta, Nunzio; Kleinschek, Melanie; Salmon, Michael
Crohn's disease (CD) is a chronic disorder of the gastrointestinal tract characterized by inflammation and intestinal epithelial injury. Loss of function mutations in the intracellular bacterial sensor NOD2 are major risk factors for the development of CD. In the absence of robust bacterial recognition by NOD2 an inflammatory cascade is initiated through alternative PRRs leading to CD. In the present study, MCC950, a specific small molecule inhibitor of NLR pyrin domain-containing protein 3 (NLRP3), abrogated dextran sodium sulfate (DSS)-induced intestinal inflammation in Nod2 −/− mice. NLRP3 inflammasome formation was observed at a higher rate in NOD2-deficient small intestinal lamina propria cells after insult by DSS. NLRP3 complex formation led to an increase in IL-1β secretion in both the small intestine and colon of Nod2 ko mice. This increase in IL-1β secretion in the intestine was attenuated by MCC950 leading to decreased disease severity in Nod2 ko mice. Our work suggests that NLRP3 inflammasome activation may be a key driver of intestinal inflammation in the absence of functional NOD2. NLRP3 pathway inhibition can prevent intestinal inflammation in the absence of robust NOD2 signaling.